Trends and Scenarios for Food Security - Rosegrant, Mark W. (2015)
"IFPRI at 40: Looking Back, Looking Forward" Special Event held on November 18, 2015. Presentation by Mark Rosegrant, Director of Environment and Production Technologies Division (EPTD) at IFPRI.